2017
DOI: 10.18632/oncotarget.14928
|View full text |Cite|
|
Sign up to set email alerts
|

The mutational landscape of ocular marginal zone lymphoma identifies frequent alterations in TNFAIP3 followed by mutations in TBL1XR1 and CREBBP

Abstract: Ocular marginal zone lymphoma is a common type of low-grade B-cell lymphoma. To investigate the genomic changes that occur in ocular marginal zone lymphoma, we analyzed 10 cases of ocular marginal zone lymphoma using whole-genome and RNA sequencing and an additional 38 cases using targeted sequencing. Major genetic alterations affecting genes involved in nuclear factor (NF)-κB pathway activation (60%), chromatin modification and transcriptional regulation (44%), and B-cell differentiation (23%) were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
69
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 49 publications
11
69
2
Order By: Relevance
“…In two patients (IBR1 and IBR3), we also found chromosome 3q amplifications that encompassed a copy number neutral loss of heterozygosity region of approximately seven million base pairs that included TBL1XR1 , a transcriptional regulator of NF‐κB and WNT signalling (Jung et al , ). Mutations of TBL1XR1 are the most frequent variants found in MYD88 wild‐type WM patients (Hunter et al , ), who show poor responses to ibrutinib monotherapy (Treon et al , ), though no somatic mutations in TBL1XR1 were identified in this study.…”
Section: Clinical and Biological Characteristics Of Waldenström Macromentioning
confidence: 88%
“…In two patients (IBR1 and IBR3), we also found chromosome 3q amplifications that encompassed a copy number neutral loss of heterozygosity region of approximately seven million base pairs that included TBL1XR1 , a transcriptional regulator of NF‐κB and WNT signalling (Jung et al , ). Mutations of TBL1XR1 are the most frequent variants found in MYD88 wild‐type WM patients (Hunter et al , ), who show poor responses to ibrutinib monotherapy (Treon et al , ), though no somatic mutations in TBL1XR1 were identified in this study.…”
Section: Clinical and Biological Characteristics Of Waldenström Macromentioning
confidence: 88%
“…For OAMZLs, data on cytogenetic abnormalities are limited: trisomy of chromosome 3 (38-62%) and 18 (14-47%) have been observed, and the latter has been associated with a higher risk of local recurrence . Jung et al, 2017.…”
Section: Cytogeneticsmentioning
confidence: 99%
“…Biased usage of IGHV genes with ongoing somatic mutations points out the pathogenetic mechanism of antigenic selection (Dagklis et al, 2012). The most frequent immunoglobulin rearrangements involve IGHV4-34 and IGHV3-23 families and are associated with auto-reactive B-cell receptors (Jung et al, 2017). A number of mutations leading to constitutive activation of NF-kB pathway, consequently promoting lymphocyte stimulation, proliferation and survival, have been detected in about 60% of the cases analyzed (Jung et al, 2017).…”
Section: Genes Involved and Proteinsmentioning
confidence: 99%
See 2 more Smart Citations